1990
DOI: 10.1038/hdy.1990.72
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom association of genes and characters found in indica × japonica hybrids of rice

Abstract: Two subspecies of common rice, indica and japonica, are distinguishable by differences in alleles at a number of loci controlling biochemical and morphological traits. The nature of associations between twelve alleles and phenotypes was studied in both a sample of varieties and hybrid populations derived from a single indica x japonica cross. Many of the associations found in varieties were not found in the F2 population. The nine sets of associations observed in F2 are explained by linkage. However, seven non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Rarely they would be intermediate type as seen in this report. This phenomenon may explain by our previous data referred as non-random association of Indica-Japonica traits (Sato et al 1990). Wild relatives also face the risk of hybridization with modern varieties.…”
Section: Hybridizationmentioning
confidence: 79%
“…Rarely they would be intermediate type as seen in this report. This phenomenon may explain by our previous data referred as non-random association of Indica-Japonica traits (Sato et al 1990). Wild relatives also face the risk of hybridization with modern varieties.…”
Section: Hybridizationmentioning
confidence: 79%
“…Although the mechanisms underlying such non-random distribution of these alleles remains to be resolved, artificial and/or natural selection, including gametic and zygotic selection, in the course of cultivar development might contribute to these results. Sato et al (1990) and Morishima (2001) reported that such gene associations were frequently found in the course of domestication and differentiation in rice. The selective advantage of the genotypes, AS2-2 SUT1-2 and also AS2-1 SUT1-1, in the past development of indica cultivars should be clarified to obtain further information for future rice breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…The indica-japonica differentiation is caused by multilocus associations. A few associations were due to linkage and easily maintained by natural or artificial selection, but most were lost in Fĝ enerations of indica x japonica hybrids (Sato, Ishikawa & Morishima, 1990). …”
Section: Association Of Traitsmentioning
confidence: 99%